2021
DOI: 10.3389/fonc.2021.627856
|View full text |Cite
|
Sign up to set email alerts
|

3,3’-Diindolylmethane Enhances Paclitaxel Sensitivity by Suppressing DNMT1-Mediated KLF4 Methylation in Breast Cancer

Abstract: Paclitaxel (PTX) is a first-line chemotherapeutic drug for the treatment of breast cancer, but drug resistance seriously limits its clinical use. The aim of the present work was to explore the effect of 3,3’-diindolylmethane (DIM) on PTX sensitivity and its possible mechanism in breast cancer. The expression of Krüppel-like factor 4 (KLF4) and DNA-methyltransferase 1 (DNMT1) in breast cancer tissues were assessed by immunohistochemistry and Western blotting. The methylation of KLF4 was evaluated by the MassARR… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
0
5
0
Order By: Relevance
“…The Kruppel-like factor 4 (KLF4), first isolated from the NIH3T3 cDNA library in 1994, is also known as GKLF [ 20 , 21 ]. As a universal transcription factor, KLF4 exists in a wide range of organisms, from zebrafish to humans, and remains highly conserved [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…The Kruppel-like factor 4 (KLF4), first isolated from the NIH3T3 cDNA library in 1994, is also known as GKLF [ 20 , 21 ]. As a universal transcription factor, KLF4 exists in a wide range of organisms, from zebrafish to humans, and remains highly conserved [ 22 ].…”
Section: Introductionmentioning
confidence: 99%
“…DNMT1 was reported to be overexpressed in the MCF-7 and T47D breast cancer cell lines [ 31 , 32 ], and its downregulation led to cell proliferation inhibition and the induction of apoptosis [ 32 ]. In line with this, our results showed that at 30 µM of TQ, mRNA expression levels of the DNMT1 gene were significantly decreased in both MCF7 and T47D cell lines ( Figure 7 A).…”
Section: Resultsmentioning
confidence: 99%
“…KLF4 induces the development of sorafenib resistance within HCC, and the inhibition of KLF4 expression with short hairpin RNA recovered the response of sorafenib-resisted HCC cell lines to sorafenib ( 223 ). The increased methylation level of CpG sites in the KLF4 promoter and decreased expression level of KLF4 in BC tissues lead to the resistance to paclitaxel, which has become the target of 3,3’-diindolylmethane in improving the effectiveness of cancer chemotherapy ( 224 ).…”
Section: Applications Of Klfs In Precision Medicinementioning
confidence: 99%